CORPORATE STRATEGY, STRATEGIC LEADERSHIP, STRATEGY IMPLEMENTATION AND COMPETITIVE ADVANTAGE : A CONCEPTUAL MODEL PROPOSAL - Yulianto, Andri Rizko; sazly, syukron; Subariyanti, Herudini; Kusumaningrum, Aliffah (Univesitas Muhammadiyah Tangerang, 2024)
Possessing a durable competitive edge is among the most crucial elements in winning commercial competitions. In the absence of this, the company will struggle to set itself apart from its rivals and will eventually go into decline. Excellence is influenced by a number of elements, such as strategic leadership, suitable strategy, and successful strategy implementation or execution. This study aims to ascertain the impact of strategic leadership, appropriate strategy, and effectiveness on the implementation or execution of strategies and how these affect the competitive advantage of organizations, particularly universities. It also generates a conceptual model about the relationship between these constructs, which will be empirically tested in subsequent studies. Through an examination of the literature and an assessment of earlier researchers' theories, the author employs a qualitative methodology. These hypotheses have been released. in approved national publications and international journals indexed by Scopus. Thus, strategic leadership and proper (enough) strategy have an impact on each other and both have an impact on the success of strategy execution, which in turn affects the competitive advantage of the firm.